Parental Involvement and its Effects on the Academic Performance of Students with Hearing Impairments - Mangubat, Jaclyn G.; Baylosis, Jaypee A.; Guinocor, Miel D.; Tenerife-Caňete, Janine Joy; Pinili, Lilibeth C. (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
The research establishes the effect of parental involvement on the academic performance of hearing-impaired students in Mandaue City. The study employed a descriptive correlational research design and collected data from 34 parents and guardians of students who enroll at Mandaue City Central Special Education School. The study examined ways in which parents support their children through activities like parenting, communicating, volunteering, learning at- home, decision making, and collaborating with community. It also examined the issues they face—i.e., psychological problems, financial problems, health problems, and social problems. The findings indicate that the majority of parents, particularly mothers between 30 and 49 years, are much involved in the children's learning. Even where such parents are undergoing financial difficulties as well as other personal challenges, they remain engaged in the education of their children. Surprisingly, no noticeable linkage was found between how involved the parents were and the difficulties they are facing in raising their children. The research indicates that although parents also encounter genuine and often demanding issues, these do not necessarily negate the possibility of them being actively engaged in the child's education. To further support these families, the research suggests an action plan comprising education workshops, peer support, and more robust collaboration between schools and communities. Finally, the study focuses on parents' resilience and significance to continue playing an active part in the learning process of their children.